Deletion of YWHAE in a patient with periventricular heterotopias and pronounced corpus callosum hypoplasia. Issue 2 (26th July 2009) - Mignon-Ravix, Cécile; Cacciagli, Pierre; El-Waly, Bilal; Moncla, Anne; Milh, Mathieu; Girard, Nadine; Chabrol, Brigitte; Philip, Nicole; Villard, Laurent
Abstract : Background: Malformations of cortical development are not rare and cause a wide spectrum of neurological diseases based on the affected region in the cerebral cortex. A significant proportion of these malformations could have a genetic basis. However, genetic studies are limited because most cases are sporadic and mendelian forms are rare. Methods: In order to identify new genetic causes in patients presenting defects of cortical organisation, array based comparative genomic hybridisation was performed in a cohort of 100 sporadic cases with various types of cortical malformations in search for inframicroscopic chromosomal rearrangements. Results: In one patient presenting with periventricular nodular heterotopias and pronounced corpus callosum hypoplasia, a small (400 kb) 17p13.3 deletion involving the YWHAE gene was identified. It is shown that YWHAE is the only brain expressed gene in the deleted region and that the other genes in the interval are unlikely to contribute to the brain malformation phenotype of this patient. Conclusion: Most 17p13.3 deletions reported to date are large, such as the deletions causing Miller–Dieker syndrome, and involve several genes implicated in various steps of brain development. Haploinsufficiency of the mouse orthologue of YWHAE causes a defect of neuronal migration. However, the human counterpart of this phenotype was not known. The case described here represents the smallest reported deletion involving the YWHAE gene and could represent the human counterpart of the abnormal cortical organisation phenotype presented by the Ywhae heterozygous knockout mouse.